2012
DOI: 10.1146/annurev-psych-120710-100419
|View full text |Cite
|
Sign up to set email alerts
|

Personality Processes: Mechanisms by Which Personality Traits “Get Outside the Skin”

Abstract: It is time to better understand why personality traits predict consequential outcomes, which calls for a closer look at personality processes. Personality processes are mechanisms that unfold over time to produce the effects of personality traits. They include reactive and instrumental processes that moderate or mediate the association between traits and outcomes. These mechanisms are illustrated here by a selection of studies of traits representing the three broad domains of personality and temperament: negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
277
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(288 citation statements)
references
References 128 publications
9
277
0
2
Order By: Relevance
“…Within each of the five domains, there are six lowerorder facets that describe personality more specifically. Studies of more specific personality traits and health-related problems have produced important findings for many years [50]. For example, Smith, Glazer, Ruiz, and Gallo [51] found that hostility, anger, and aggressiveness are related to cardiovascular problems.…”
Section: Discussionmentioning
confidence: 99%
“…Within each of the five domains, there are six lowerorder facets that describe personality more specifically. Studies of more specific personality traits and health-related problems have produced important findings for many years [50]. For example, Smith, Glazer, Ruiz, and Gallo [51] found that hostility, anger, and aggressiveness are related to cardiovascular problems.…”
Section: Discussionmentioning
confidence: 99%
“…erally unrelated to life-events in the German Socioeconomic Panel, it was related to starting one's first job and becoming unemployed (Specht et al, 2011), and C is consistently associated with job performance (Hampson, 2012;Ozer & Benet-Martinez, 2006). It may be, though, that results from this large German sample would not generalize to the United States, where a larger percentage of the population is marginalized (e.g., impoverished) and thus more susceptible to the occurrence of life-events and their negative effects.…”
Section: Avoidance and Neutralization Of Stressorsmentioning
confidence: 99%
“…We only assessed each construct at one time point. Longitudinal designs in which personality, situations, and behaviors can be assessed at multiple times points yield more reliable findings than cross-sectional designs that assess these constructs at a single point in time (Hampson, 2011;Nesselroade, 2007). In future research we plan to use a weekly online diary method (Bolger, Davis, & Rafaeli, 2003;Iida, Shrout, Laurenceau, & Bolger, 2012) to assess interpersonal conflict at work and CWB at Guilt Proneness and CWB 17 multiple time points.…”
Section: Guilt Proneness and Cwb 16mentioning
confidence: 99%